The Rules Of Feedback In Writing Class - Vitri Angraini Hardi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2020)
Producing a writing in Foreign Language is struggle for foreign language learners in Indonesia mostly. The difference on various linguistic aspects, mechanics and language usage are the source of the difficulties in composing a writing. However, language learners are required to master the four skills in English, included writing. The way to facilitate the students in order to compose a writing is through Teaching and Learning process. The teacher as the person who has responsibility to enhance the learning have to create the way to motivate the students to produce a writing. One of the way to facilitate the students is by giving feedback on students’ writing. The teacher are asked to use various kinds of feedback to guide the students to produce a good writing